Growth and nutritional status, and their association with lung function: a study from the international Primary Ciliary Dyskinesia Cohort. Issue 6 (21st December 2017) - Goutaki, Myrofora; Halbeisen, Florian S.; Spycher, Ben D.; Maurer, Elisabeth; Belle, Fabiën; Amirav, Israel; Behan, Laura; Boon, Mieke; Carr, Siobhan; Casaulta, Carmen; Clement, Annick; Crowley, Suzanne; et al.
Chronic respiratory disease can affect growth and nutrition, which can influence lung function. We investigated height, body mass index (BMI), and lung function in patients with primary ciliary dyskinesia (PCD). In this study, based on the international PCD (iPCD) Cohort, we calculated z-scores for height and BMI using World Health Organization (WHO) and national growth references, and assessed associations with age, sex, country, diagnostic certainty, age at diagnosis, organ laterality and lung function in multilevel regression models that accounted for repeated measurements. We analysed 6402 measurements from 1609 iPCD Cohort patients. Height was reduced compared to WHO (z-score −0.12, 95% CI −0.17 to −0.06) and national references (z-score −0.27, 95% CI −0.33 to −0.21) in male and female patients in all age groups, with variation between countries. Height and BMI were higher in patients diagnosed earlier in life (p=0.026 and p<0.001, respectively) and closely associated with forced expiratory volume in 1 s and forced vital capacity z-scores (p<0.001). Our study indicates that both growth and nutrition are affected adversely in PCD patients from early life and are both strongly associated with lung function. If supported by longitudinal studies, these findings suggest that early diagnosis with multidisciplinary management and nutritional advice could improve growth and delay disease progression and lung function impairment in PCD. Multidisciplinary management and nutritional advice could improve growth and delay lung function impairment in PCD http://ow.ly/5iQz30gB4Mo